Evaluation of Inpatient Antibiotic Use at Hospital X, Semarang Regency, in 2023 Using Quantitative Methods - Ivana; Avianti Eka Dewi Aditya Purwaningsih; Fadhila Shaumi Chunaesiana (Fakultas Farmasi Institut Kesehatan Medistra Lubuk Pakam, 2025)
Background: Antibiotic resistance is a critical global health problem resulting from the inappropriate use of antibiotics. Understanding the pattern of antibiotic utilization is necessary to support rational prescribing and reduce resistance.Objective: This study aimed to evaluate the pattern of antibiotic use among inpatients at Hospital X in Semarang Regency in 2023. Methods: A retrospective study was conducted among inpatients aged 19–59 years who received antibiotic therapy between January and December 2023. Data were analyzed using the Anatomical Therapeutic Chemical/Defined Daily Dose method and Drug Utilization 90% to assess consumption patterns. Results: A total of 1,402 patients were included, with most patients being female and within the 49–59 age group. The majority of hospital stays lasted 1–5 days. Ceftriaxone injection is the most frequently used antibiotic and records the highest defined daily dose, followed by levofloxacin and ampicillin sulbactam. Conclusion: The study shows that ceftriaxone injection dominates antibiotic utilization. Regular evaluation using standardized methods is essential to ensure appropriate use and prevent resistance. Antibiotic procurement policies should be guided by actual consumption data to improve efficiency in drug management.